Advanced gestational trophoblastic disease: A case report of medical management prior to surgical intervention - Ann Lehto; Kyle Hitscherich; Olga Argeros (Elsevier, 2018)
Background: Gestational trophoblastic disease (GTD) is a rare developmental form of proliferative trophoblastic tissue. Sparse literature exists regarding the optimal management of patients with advanced GTD, but the definitive treatment is urgent surgical intervention. Case: A 48-year-old woman presented advanced GTD. She was medically managed for hypertension and hyperthyroidism prior to surgical intervention in order to minimize the risk of anesthetic and surgical complications. Conclusion: Advanced GTD is rare. Undetected GTD can result in complications such as thyrotoxicosis, which poses substantial risks in the peri-operative period. Appropriate identification and management of this clinical problem are essential to prevent complications as well as subsequent malignant sequelae. Keywords: Molar pregnancy, Hydatidiform mole, Thyrotoxicosis, Medical optimization